Investigation of Active Compounds in Vetiver Oil against Penicillin-Binding Protein 1 of Acinetobacter baumannii: A Bioinformatics Approach - Yulianto Ade Prasetya; Putri Setyawati; Mariana Wahjudi; Tjie Kok (Postgraduate, University of Mataram, 2026)
Acinetobacter baumannii is responsible for various infections in humans and is well known for its ability to develop antibiotic resistance. Therefore, exploring natural compounds, such as those found in vetiver oil, is crucial. Vetiver oil contains numerous compounds, including sesquiterpenes and sesquiterpenols; however, their activity against A. baumannii has not been previously reported. This research aims to investigate the potential of vetiver oil compounds in inhibiting penicillin-binding protein 1 (PBP1) in Acinetobacter baumannii using a bioinformatics approach. The methodology involved obtaining the 3D structure of PBP1 from the Protein Data Bank (PDB), while vetiver oil compounds were retrieved from the PubMed database. The first screening was conducted using ADMET Lab 3.0 to assess drug-likeness parameters, absorption, distribution, metabolism, excretion, and toxicity. The best-screened compounds were further evaluated through molecular docking using the Proteins Plus webserver to determine the binding residues. The results showed that vetiver oil compounds, including nootkatone, khusimol, and vetivenic acid, formed hydrogen bonds and hydrophobic interactions. Nootkatone, khusimol, and vetivenic acid have potential as inhibitors of PBP1; however, further in vitro studies are required to directly assess their biological activity and effectiveness.